PEMANFAATAN BATANG PISANG SEBAGAI MEDIA TANAM DI DESA PULAU GODANG KARI, KECAMATAN KUANTAN TENGAH, KABUPATEN KUANTAN SINGINGI - Dadang Mashur; Indah Kusuma; Puput Azizah Heriyana; Rani Pratiwi Nugraha; Rahmat Viki; Dores Putra Utama; Maryam Nur Arifah; Muhammad Hafizh; Natasya Ilya Sahira; Nawrah Dwi Latifah; Susi Rahayu (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Many people ignore the part of the banana stem, even though the banana stem also has various benefits. One of the uses in utilizing banana stems is to use banana stems as a container instead of polybags for planting media. This study aims to see banana stems as a suitable planting medium for plant growth and yield. In community service, socialization was carried out in Pulau Godang Kari Village to implement community service programs by involving the local village community. This study used 2 factors, namely banana stem factors and planting media factors, namely soil fermentation, manure, compost, and rice husks. The results of this study indicate fertility in plants, due to the nutrients contained in the banana stem.